Exploring Cultural Horizons: Connecting Australian Students with Asian Students via Video-Conferencing - Reading, Chris; Auh, Myung-Sook; Pegg, John; Cybula, Peter (Australian and International Journal of Rural Education, 2013)
The need for Australian school students to develop a strong understanding of Asian culture has been recognised in the cross-curriculum priority, Asia and Australia's Engagement with Asia, of the Australian Curriculum. School students in rural and remote Australia have limited opportunities to engage with Asians and learn about their culture. The Australia-Korea ConneXion (AKC) Program digitally connects Australian and Korean schools to develop cultural exchange. In particular, lessons incorporating videoconferencing enable interactions that enhance the cultural values and attitudes of the students involved. While recognising the potential of videoconferencing to enrich their students‘ experiences of other cultures, teachers in rural and remote schools may not feel confident in the practicalities of incorporating videoconferencing into lessons to connect their students with students in other countries. This paper aims to inform teachers on the analysis of AKC Program lessons utilising videoconferencing. Although there is a cultural focus, each pair of teachers has flexibility in the choice of lesson content. Guidance is provided for teachers who might want to begin videoconferencing with classes in another country, including steps from making first contact with the teacher to planning the learning, setting up the technology and finally facilitating the lessons. As part of research evaluating this program, a rubric was developed to code the quality of a videoconferencing lesson. Analysis of data from lessons between four pairs of schools provides insight into the videoconferencing lessons and a range of pedagogical and technological advice to assist teachers to improve the quality of their future use of videoconferencing to connect students and allow them to explore new cultural horizons.